HUBUNGAN ANTARA CELEBRITY WORSHIP TERHADAP SUBJECTIVE WELL-BEING PADA REMAJA PENGGEMAR K-POP - Laksono Septhallia Anjani; Wibowo Doddy Hendro (Bajang Institute, 2023)
Many teenagers and adults are now K-pop fans. Being a kpop fan can make someone feel happy, scared or sad. So this can affect the subjective well-being of someone who likes Kpop. This can also be caused by fans who love their idol celebrities too much to the point that fans are very obsessed with their idol celebrities or usually known as Celebrity Worship. This research was designed to determine the relationship between celebrity worship and subjective well-being among teenage K-pop fans. The approach used in this research is quantitative with a correlational and comparative design. To obtain data, this research used a sample of 55 teenagers from the Fortune Entertainment Cirebon cover dance community, who were selected using a purposive sampling technique with the criteria being that the youth were 15-21 years old and were members of the Fortune Entertainment community. The results obtained in this study obtained a correlation coefficient value for the Celebrity Worship and Subjective Well Being variables of r= -0.387 with a sig value = 0.004 (p<0.05). This shows that there is a negative relationship between Celebrity Worship and Subjective Well Being. So it is hoped that individuals who like K-Pop will act naturally when they like their idol artists.